(untitled) (Szociológiai Szemle, 2024)
The unemployed who try to create their own job may get different kinds of support from the Employment Fund. The results of the survey summarized in this paper studied the chances of survival of enterprises founded by some unemployed. It was revealed by the survey that quite an unexpected proportion of supported enterprises, that is, almost three-quarters were able to remain operative even six to eight months after the subsidies were stopped and the improvement of their ability to offer sustenance has also improved. However, if the result is seen from the angle of how much would have been accomplished without subsidy, the picture is more disheartening: it was unnecessary to give financial incentives to more than two-thirds of the respondents because they would have chosen the way of self-employment even without support.